Addressing the Core-Periphery Imbalances in Europe: Resource Misallocation and Expansionary Fiscal Policies - Luigi Bonatti; Andrea Fracasso (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
How can the euro area tackle its perennial problems of core/periphery imbalances and anaemic long-term growth? According to network members Luigi Bonatti and Andrea Fracasso, Università di Trento, there is no quick-fix solution. Temporary fiscal stimulus does not produce permanent improvements, while the upfront costs and short-term negative impact of structural reforms can feed distributional conflicts. Permanent cross-national transfers provide local relief, but also exacerbate tensions among member states. The authors advocate a nuanced approach focused on the key role of structural differences in affecting income and growth differentials, as well as competitive imbalances across the euro area.
Keywords: 330